Hazardous air pollutants and asthma. - Leikauf, George D (2002)
Asthma has a high prevalence in the United States, and persons with asthma may be at added risk from the adverse effects of hazardous air pollutants (HAPs). Complex mixtures (fine particulate matter and tobacco smoke) have been associated with respiratory symptoms and hospital admissions for asthma. The toxic ingredients of these mixtures are HAPs, but whether ambient HAP exposures can induce asthma remains unclear. Certain HAPs are occupational asthmagens, whereas others may act as adjuncts during sensitization. HAPs may exacerbate asthma because, once sensitized, individuals can respond to remarkably low concentrations, and irritants lower the bronchoconstrictive threshold to respiratory antigens. Adverse responses after ambient exposures to complex mixtures often occur at concentrations below those producing effects in controlled human exposures to a single compound. In addition, certain HAPs that have been associated with asthma in occupational settings may interact with criteria pollutants in ambient air to exacerbate asthma. Based on these observations and past experience with 188 HAPs, a list of 19 compounds that could have the highest impact on the induction or exacerbation of asthma was developed. Nine additional compounds were identified that might exacerbate asthma based on their irritancy, respirability, or ability to react with biological macromolecules. Although the ambient levels of these 28 compounds are largely unknown, estimated exposures from emissions inventories and limited air monitoring suggest that aldehydes (especially acrolein and formaldehyde) and metals (especially nickel and chromium compounds) may have possible health risk indices sufficient for additional attention. Recommendations for research are presented regarding exposure monitoring and evaluation of biologic mechanisms controlling how these substances induce and exacerbate asthma.